Biofilm material based triboelectric nanogenerator with high output performance in 95% humidity environment. (November 2020) - Wang, Nannan; Zheng, Youbin; Feng, Yange; Zhou, Feng; Wang, Daoai
Abstract: Moisture in environment can severely decrease the output of the solid-solid triboelectric nanogenerators (TENGs) which usually hinders their further practical applications. To solve this problem, in this paper we fabricated a new type of biofilm materials based TENG, which can work stably in high humidity environment with high output performance by forming hydrogen bond with water molecules. In high humidity environment the hydroxyl-rich biomaterials, such as starch molecules, and water molecules could form hydrogen bonds spontaneously to fix water molecules on the surface, which allows water molecules to participate in triboelectric charging as a more electropositive material to obtain a higher output of TENG. Different from the traditional polymer materials based TENGs, the output of the starch films based TENG increases with the increase of the environmental humidity. The output current and voltage could increase from 6.2 μA to 110 V to 16.6 μA and 330 V with the ambient humidity increasing from 15% to 95%, respectively, which is about 12 times larger than that of the traditional nylon-11 based TENG in the humidity of 95%. It is an important supplement of TENG family and highly expand application scopes for energy harvesting and self-powered sensors in high humidity environment, especially in cloudy, foggy days or under water and sweat conditions. Graphical abstract: A new kind of biofilm material based triboelectric nanogenerator (TENG) with high output performance is constructed for energy harvesting in high humidity environment, solving the output reduction of solid-solid TENG with the increase of environmental humidity. This type of TENG has promising potential applications in energy harvesting, self-powered electronic devices early warning devices in fog, ocean, and other high humidity environment. Image 1 Highlights: This new type of triboelectric nanogenerator can work stably in high humidity environment with high output performance. This TENG is fabricated with an environment friendly and biodegradable hydroxyl-rich material without any specific treatment. Biofilm materials based TENGs have universal characteristics of high output under high humidity.